Mechanisms of myocardial ischemic injury repair by bone marrow mesenchymal stem cell-derived miR-183-5P targeting FOXO1: bone marrow mesenchymal stem cell-derived miR-183-5P - Quancheng Lin; Jian Liu; Qingyang Chen; Yan Li; Feiyue Dai; Xinyu Chen (Cellular and Molecular Biology, 2023)
The homing rate of transplanted mesenchymal stem cells (BMSCs) after acute myocardial infarction (AMI) is generally low, with only 0%-6% of the number of transplanted stem cells distributed to the heart; therefore, this study will investigate the therapeutic effects and mechanisms of miR-183-5p-modified BMSCs cells on myocardial ischemia and hypoxia caused by AMI. In this experiment, After first establishing the BMSCs ischemic-hypoxic injury model, the rats were divided into healthy group, model group, BMSCs group and BMSCs+ miR-183-5P group, where the healthy group was taken to normal culture, the model group caused myocardial ischemic-hypoxic damage, the BMSCs group underwent BMSCs stem cell transplantation on the basis of the model group, and the BMSCs+ miR-183-5P group was group was cultured with BMSCs-derived miR-183-5P on the basis of the model group. Myocardial tissue sections of rats in each group were taken for HE staining and histopathological changes were observed by light microscopy. The proliferation, apoptosis and migration ability of the cells were detected by CCK-8 method, flow cytometry and Transwell transfer method. The target gene of miR-183-5P was predicted using bioinformatics software, and the binding of miR-183-5P to FOXO1 was investigated. The expression of FOXO1 was analysed using qRT-PCR and protein blotting techniques. The qRT-PCR results showed that the expression of miR-183-5P was higher in BMSCs of the BMSCs group and BMSCs+ miR-183-5P group compared with the model group, and the expression was highest in the BMSCs+ miR-183-5P group (P<0.05). The value-added ability and the migration capacity of BMSCs in the BMSCs group and BMSCs+ miR-183-5P group were increased compared with the model group, and the BMSCs+ miR-183-5P group BMSCs had the highest proliferation capacity and the migration capacity(P<0.05). In contrast, the apoptotic capacity of BMSCs was significantly reduced in the BMSCs group and BMSCs+ miR-183-5P group compared with the model group, and the apoptotic capacity of BMSCs was lowest in the BMSCs+ miR-183-5P group (P<0.05). The bioinformatics software RegRNA 2. 0 was used to predict that the specific target gene that may be regulated by miR-183-5P is FOXO1 and confirmed that miR-183-5P does indeed have a targeting relationship with the FOXO1 pathway. After upregulation of miR-183-5P expression, the expression of FOXO1 mRNA was higher in BMSCs of the BMSCs group and BMSCs+ miR-183-5P group compared with the model group, and the expression was highest in the BMSCs+ miR-183-5P group (P<0.05). The Western blotting showed that the expression of FOXO1 mRNA was higher in BMSCs of the BMSCs group and BMSCs+ miR-183-5P group compared with the model group, especially the expression was highest in the BMSCs+ miR-183-5P group (P<0.05). In conclusion, BMSCs-derived miR-183-5P can target and regulate FOXO1 to increase the proliferation and migration of BMSCs and reduce their apoptosis, and can also reduce myocardial tissue edema and inflammatory response by increasing the expression of FOXO1 mRNA, which can increase the survival rate of BMSCs and provide a clinical basis for BMSCs transplantation.